Prevalence and Pattern of Dermatoses During Pregnancy - Kabir, Md Humayun; Latif Khan, Md Abdul; Islam Khan, Md Shirajul; Karim, ATM Rezaul (Sir Salimullah Medical College Journal, 2022)
Background: Pregnancy is a physiological status of a woman. Every organ is adapting in order to accept another human body. Many skin changes during pregnancy are considered to be normal or physiological but few dermatoses occurring in pregnancy may severely affect the mother as well as the fetus. Early diagnosis and treatment may help to reduce morbidity and mortality to the gravid patient and her fetus and minimize fetal exposure to unnecessary treatment. Objective: To determine the pattern of dermatoses during pregnancy. Materials and Methods: One hundred sixteen pregnant women of different trimester were selected out of 1674 according to the exclusion and inclusion criteria for this study. Detailed history, clinical examination and relevant investigations were done in all patients. Results: This clinical study shows about 6.9% pregnant women had specific dermatoses. Maximum 44(37.9%) women were in between the age of 25 to 29 years. According to trimester 69(59.48%) patients were in third trimester. In case of gravid maximum 68(58.62%) patients were primigravida. In this study pruritic urticarial papules and plaques of pregnancy (PUPPP) was the most common dermatoses during pregnancy. Conclusion: A pregnant woman with a pruritic skin eruption requires immediate evaluation and diagnosis because delayed diagnosis or misdiagnosis may pose significant risk to the fetus and the mother. It is necessary to know how to diagnosis and treat this condition to establish a better outcome for the mother and the fetus. Sir Salimullah Med Coll J 2022; 30: 46-50